The Impact of Education and Training on State Civil Apparatus Performance at The Banggai Regency Population and Civil Registration Service - Rahmad; Andi Hartati; Sriwindari Pasman (Program Studi Ilmu Pemerintahan, FISIP - Universitas Halu Oleo, 2022)
This study aims to examine the effect of education and training of encriesing knowledge, expertise, skills, and attitudes on the performance of the state civil apparatus. The Empirical analysis was conducted using a sample of 50 state civil apparatus at the Banggai Regency Population and Civil Registration Service. This Study used a questionnaire for the data collection. After passing reliability and validity test, the data were analyzed with pearson Product moment correlation and Simple Linear Regression. The result show that education and training has positive and significant direct influence on state civil apparatus performance. however the price of the correlation coefficient obtained (test r) = 0.378 of the calculated r-price, this means that it gives the consequence that there is a positive influence education and training of State civil apparatus performance and the Significance level of 0.05 95% confidence level for a one-sided test in the t-distribution. This study has shown a of more comprehensive effect of education and training of state civil apparatus of knowledge, Expertise and attitudes.